2015
DOI: 10.1038/ncomms7824
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing grain boundary ionic conductivity in mixed ionic–electronic conductors

Abstract: Mixed ionic–electronic conductors are widely used in devices for energy conversion and storage. Grain boundaries in these materials have nanoscale spatial dimensions, which can generate substantial resistance to ionic transport due to dopant segregation. Here, we report the concept of targeted phase formation in a Ce0.8Gd0.2O2−δ–CoFe2O4 composite that serves to enhance the grain boundary ionic conductivity. Using transmission electron microscopy and spectroscopy approaches, we probe the grain boundary charge d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
125
0
5

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 216 publications
(137 citation statements)
references
References 55 publications
7
125
0
5
Order By: Relevance
“…in the paper by Lin et al [24] the authors show how a lower ionic conductivity at grain boundaries as compared to that of the grains leads to the decrease of the total ionic conductivity of Gd-doped ceria. Therefore, for an idealized model, considered in this as well as in previous theoretical works [8], the calculated conductivity should correspond to, at least, the upper limit for the experimental results.…”
Section: E Temperature Dependence Of Conductivitymentioning
confidence: 99%
“…in the paper by Lin et al [24] the authors show how a lower ionic conductivity at grain boundaries as compared to that of the grains leads to the decrease of the total ionic conductivity of Gd-doped ceria. Therefore, for an idealized model, considered in this as well as in previous theoretical works [8], the calculated conductivity should correspond to, at least, the upper limit for the experimental results.…”
Section: E Temperature Dependence Of Conductivitymentioning
confidence: 99%
“…Rather novel strategies that prevent dopant segregation need to take prime focus. 94,135 In the doped heterostructures, thickness of layers may also need to be optimized so as to induce maximum tensile strain while simultaneously reducing the large dopant concentration at interfaces. There are some studies that have indicated a layer-thickness dependence peak in oxygen conductivity, showing that maximum conductivity does not necessarily occur in the thinnest structures.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, scanning transmission electron microscopy (STEM) coupled with electron energy loss spectroscopy (EELS) is capable of simultaneously mapping the atomic/electronic structure of light elements such as oxygen at adequate spatial resolution. The electronic state of the elements across the boundary can be identified by STEM-EELS line scan crossing the grain boundary in steps of a few nanometres [32]. TEM imaging further resolves details of the crystal structure of grains and grain boundaries.…”
Section: Transmission Electron Microscopementioning
confidence: 99%